The role of tyrosine hydroxylase-dopamine pathway in Parkinson's disease pathogenesis - Zhou, Zhi Dong (2023)
Background: Parkinson’s disease (PD) is characterized by selective and progressive dopamine (DA) neuron loss in the substantia nigra and other brain regions, with the presence of Lewy body formation. Most PD cases are sporadic, whereas monogenic forms of PD have been linked to multiple genes, including Leucine kinase repeat 2 (LRRK2) and PTEN-induced kinase 1 (PINK1), two protein kinase genes involved in multiple signaling pathways. There is increasing evidence to suggest that endogenous DA and DA-dependent neurodegeneration have a pathophysiologic role in sporadic and familial PD. Methods: We generated patient-derived dopaminergic neurons and human midbrain-like organoids (hMLOs), transgenic (TG) mouse and Drosophila models, expressing both mutant and wild-type (WT) LRRK2 and PINK1. Using these models, we examined the effect of LRRK2 and PINK1 on tyrosine hydroxylase (TH)–DA pathway. Results: We demonstrated that PD-linked LRRK2 mutations were able to modulate TH–DA pathway, resulting in up-regulation of DA early in the disease which subsequently led to neurodegeneration. The LRRK2-induced DA toxicity and degeneration were abrogated by wild-type (WT) PINK1 (but not PINK1 mutations), and early treatment with a clinical-grade drug, α-methyl-L-tyrosine (α-MT), a TH inhibitor, was able to reverse the pathologies in human neurons and TG Drosophila models. We also identified opposing effects between LRRK2 and PINK1 on TH expression, suggesting that functional balance between these two genes may regulate the TH–DA pathway. Conclusions: Our findings highlight the vital role of the TH–DA pathway in PD pathogenesis. LRRK2 and PINK1 have opposing effects on the TH–DA pathway, and its balance affects DA neuron survival. LRRK2 or PINK1 mutations can disrupt this balance, promoting DA neuron demise. Our findings provide support for potential clinical trials using TH–DA pathway inhibitors in early or prodromic PD.